Incorporating critical thinking skills in English classroom instruction: a case study of Indonesian preservice teachers - Imaniar, Fahmy; Rakhmawati, R (Universitas Muhammadiyah Purwokerto, 2024)
Critical thinking is an essential skill in education due to the demands of the 21st century, especially in the English as a Foreign Language (EFL) classroom. Nonetheless, the inclusion of critical thinking in English classroom can be quite challenging, particularly for pre-service teachers. This research deals with the integration of critical thinking into teaching modules conducted by pre-service English teachers at UIN Sunan Ampel Surabaya, focusing on lesson plan and instructional method. The study used a case study approach, analyzing teaching modules of twelve pre-service teachers. Bloom's taxonomy and a five-step critical thinking model were used to see the incorporation of critical thinking skills in their teaching modules. Interview was also carried out to elicit information on their way of incorporating critical thinking in their English instruction as related to the document analyzed. The results shows that the pre-service teachers exercised natural, effective thinking through well-defined objectives, questioning method, practical learning with feedback and reflection as a way to incorporate critical thinking through their teaching module. The result that they are aware of their role in supporting the students in developing their critical thinking while teaching English. The implications of the insights from the study signal considerable potential contributions for increased structured approaches to critical thinking instruction in EFL and a general commitment to reflective practice and responsive lesson design in English Language Teaching. The results have important implications for the integration of language education with critical thinking so that students become equipped with essential skills required in the 21st century.